Non-uniform microstrip antenna array for DSRC in single-lane structures - Varum, Tiago (2017)
Vehicular communications have been subject to a great development in recent years, with multiple applications, such as electronic payments, improving the convenience and comfort of drivers. Its communication network is supported by dedicated short range communications (DSRC), a system composed of onboard units (OBU) and roadside units (RSU). A recently conceived different set-up for the tolling infrastructures consists of placing them in highway access roads, allowing a number of benefits over common gateway infrastructures, divided into several lanes and using complex systems. This paper presents an antenna array whose characteristics are according to the DSRC standards. Additionally, the array holds an innovative radiation pattern adjusted to the new approach requirements, with an almost uniform wide beamwidth along the road width, negligible side lobes, and operating in a significant bandwidth.